Pengaruh Metode Belajar dan Koordinasi Mata-Kaki Terhadap Keterampilan Lompat Jauh - A, Muh Faisal Lutfi; Wasan, Aan; Junaidi, Junaidi (Journal Sport Area, 2019)
The purpose of this research is to examine the effect of the overall and part learning methods and the eye-to-foot coordination towards leap skills on long jumps of senior high school students. This research is conducted on students of SMA Negeri 2 Sinjai. In this study, the researcher uses a treatment by the level of 2 x 2. The sample consists of 40 students that divided into four groups, each of them consists of 10 students. The technique of analysis uses two-way variance (ANOVA) and then it is continued with Turkey test at significance level α = 0,5. The results of this study indicate that (1) the overall learning method has a better effect than the part learning method towards long jump skills. (2) there is an interaction result between the overall and part learning method and the eye-foot coordination towards the result of long jump skills. (3) the overall learning method has a better effect than the part learning method that has high coordination. (4) the overall learning method has a better effect than the part learning methods that has low eye-foot coordination